INCREASING SENSITIVITY OF MCF-7/DOX CELLS TOWARDS DOXORUBICIN BY HESPERETIN THROUGH SUPPRESSION OF P-GLYCOPROTEIN EXPRESSION - Sarmoko, .; Pamungkas P, Dyaningtyas Dewi; Susidarti, Ratna Asmah; Nugroho, Agung Endro; Meiyanto, Edy (Indonesian Journal of Pharmacy, 2014)
Long-term use of doxorubicin causes cancer resistance due to overexpression of P-glycoprotein (P-gp), a protein that plays a role in cell drug efflux. The purpose of this study is to determine the action of hesperetin in increasing the cytotoxicity of doxorubicin on MCF-7 cancer cells resistant to doxorubicin (MCF-7/DOX) through suppression of P-gp expression. Cytotoxic assay of single and combinational treatment of doxorubicin and hesperetin were performed by using MTT assay. Apoptosis evidence was examined by using double staining with acridine orange and ethidium bromide dyes, while Pgp expression was determined by using immunocytochemistry. Hesperetin reduced cell viability in dose dependent manner. Both MCF-7 ori and MCF-7/DOX cells gave different responses to hesperetin with the IC50 values of >500Î¼M and 267Î¼M, respectively. Combining treatment of hesperetin and doxorubicin to MCF-7/DOX cells at the dose of 95Î¼M and 230nM increased apoptosis evidence and suppressed P-gp expression. These results suggest that hesperetin enhances the anticancer effect of doxorubicin to resistance MCF-7 cells through suppression of P-gp expression.